2003
DOI: 10.1002/cncr.11321
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and early‐stage melanoma

Abstract: BACKGROUND Cutaneous melanomas are aggressive tumors with an unpredictable biologic behavior. It has been suggested that women who present with melanoma during pregnancy have a worse prognosis due to more aggressive behavior of the melanoma. The objective of the current study was to evaluate the long‐term effect of pregnancy on disease progression in women with Stage I–II melanoma. METHODS From 1965 to 2001, 46 pregnant women were treated for a Stage I–II melanoma at the University Medical Center Groningen. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 26 publications
4
63
0
Order By: Relevance
“…In the study of Slingluff et al (Slingluff et al, 1990) there was no difference in the survival time, but pregnant patients were presented with a larger number of involved lymph nodes (39% versus 26%, p=0.053) at diagnosis, lymph node metastases appeared in shorter interval after the diagnosis of stage I disease (p=0.021), and shorter disease free survival (DFS). The results of following studies have not reported difference in survival among pregnant patients (MacKie et al, 1991;Stein et al, 1990;Driscoll et al, 1993;Travers et al, 1995;Grin et al, 1996;Daryanani et al, 2003), but in some a caution has been stressed to the diagnosis of thicker melanoma in pregnancy (MacKie et al, 1991;Travers et al, 1995). In already mentioned Lens et al study (Lens et al, 2004) (Figure 2.…”
Section: Impact Of Pregnancy To Melanoma Prognosismentioning
confidence: 98%
“…In the study of Slingluff et al (Slingluff et al, 1990) there was no difference in the survival time, but pregnant patients were presented with a larger number of involved lymph nodes (39% versus 26%, p=0.053) at diagnosis, lymph node metastases appeared in shorter interval after the diagnosis of stage I disease (p=0.021), and shorter disease free survival (DFS). The results of following studies have not reported difference in survival among pregnant patients (MacKie et al, 1991;Stein et al, 1990;Driscoll et al, 1993;Travers et al, 1995;Grin et al, 1996;Daryanani et al, 2003), but in some a caution has been stressed to the diagnosis of thicker melanoma in pregnancy (MacKie et al, 1991;Travers et al, 1995). In already mentioned Lens et al study (Lens et al, 2004) (Figure 2.…”
Section: Impact Of Pregnancy To Melanoma Prognosismentioning
confidence: 98%
“…No difference was found in the 10-year disease-free and overall survival rates between the pregnant and non-pregnant groups. Survival depends on tumour thickness and the presence of ulceration (8). Previous pregnancy can exert some favourable influence on prognosis; women with at least one pregnancy had a 94% probability of surviving melanoma compared to nulliparous women, of whom only 83% survived (9).…”
Section: Abstract öZetmentioning
confidence: 99%
“…33 More recently, a study from Germany highlighted that pregnancy did not appear to have an adverse long-term effect on survival in patients with clinically localized melanoma. 34 Currently, there is broad agreement that prognosis for women with melanoma during pregnancy, just as for nonpregnant women and for men, is primarily dependent on tumor thickness and ulceration.…”
Section: Epidemiology Diagnosis Screening and Prognosismentioning
confidence: 99%